Characterization of an Eighteenth-Century Wooden Icon from the Ethnographic Museum of Transylvania. (1st November 2016) - Moldovan, Z.; Bratu, I.; Marutoiu, C.; Kacso, Irina; Trosan, Laura; Pop-Toader, Daniela; Nemes, Olivia Florena; Tanaselia, C.
ABSTRACT: Here is reported the characterization of a religious art object from Transylvania. The object is a wooden icon named Circumcision and represents scenes from the Old Testament and is from the Rebrişoara wooden church, Bistriţa County. It was painted in the eighteenth century by unknown artists. The object has some degradation, and the wooden background has some fungal and/or xylophagous damage. The wood was determined to be lime, and its condition was characterized by infrared spectroscopy and differential scanning calorimetry. The presence of oxalate was caused by wood decay. The paint was characterized by X-ray fluorescence and infrared spectroscopy to include gypsum, aliphatic, an egg yolk degradation product, lead carbonate, and lead-minium. The binder was characterized by direct introduction-mass spectrometry to contain paraffin, fatty acids, and cholesteryl ester.